THE EFFECT OF THE APPLICATION OF LOGIC GATE LEARNING MEDIA IT-BASED TO IMPROVE MOTIVATION AND LEARNING OUTCOMES STUDENTS - Yanie, Ahmad; Junaidi (JMRI Journal of Multidisciplinary Research and Innovation, 2024)
This research aims to determine the application of learning media IT-based logic gates to improve student motivation and learning outcomes. This research is in the form of quantitative research. Sample used one class, taken using a sampling technique saturated with classes Before the treatment (pretest) taught by conventional methods / lectures and classes after treatment (posttest) is taught with IT-based logic gate learning media, namely Macromedia Flash. Data collection techniques using test methods and methods documentation for student learning outcomes data. Data analysis techniques using t-tests. The test criterion is if the questionnaire score filled is greater than the mean, then the student This is included in the criteria for motivation and vice versa, if the questionnaire value smaller than the mean, the student is included in the criteria unmotivated. From the results of the analysis, there were 15 students and 2 students who unmotivated. This hypothesis test is carried out using a t-test against the result value learn before treatment (pretest) and after treatment (posttest) with using a t-test with a significant level of 5%. The test criteria are as follows: H0 Accepted / H1 rejected if tcount< ttable and H0 rejected / H1 accepted if tcount > ttable. From the results Analysis of the hypothesis test obtained tcount = 12.33 and t table = 1.746 Because tcount > ttable. By test the hypothesis obtained t count (12.33) > ttable (1.746) then H0 is rejected